PERAN LOGIKA BERFIKIR SECARA KRITIS DALAM MENANGGAPI BERITA HOAX DI KALANGAN MASYARAKAT - Liska Kala’ Sendong; Nalce Lante, Santi, Detriyanti Bangian, Irma (Jurnal Komunikasi, 2024)
Thinking critically is a skill that can be used in dealing with a problem at hand. Critical Thinking is a reasoning process that is carried out by someone by seeking information before drawing a conclusion. In this paper, we will review how to think critically in responding to hoax news. Apart from that, it will also discuss how to think critically using logic as well as the characteristics and benefits of critical thinking in responding to hoax news. And the final part of this article describes the application of critical thinking in processing news circulating today. The purpose of this writing is how one can think critically and also reduce the level of hoax news. Critical thinking in managing hoax news at this time can be done with a series of concepts in thinking to see a news, how should someone think logically and critically in responding to a news and then making a decision on the news that is circulating